Petrology of the Lower Succession of Injana Formation, Shorr Shareen area, Wasit Governorate, - Eastern Iraq - almaliky, yasmeen abdulmutaleb; Tamar- Agha, Mazin Y.; Jasim, Hasan K. (Iraqi Journal of Science, 2022)
This study deals with the petrology of the lower succession of the Injana Formation in the Shorr Shareen area, Wasit Governorate, Eastern Iraq. The study revealed that the sandstone is litharenite consists of 45.56% rock fragments, 22.13% quartz and 8.5% feldspars. The matrix is about 8.39%, consisting of silt and clay particles. The cement is variable (carbonates 8.42%, evaporites 1.78% and iron oxides 0.96%). The grain assemblage infers that the source of the rock fragments is nearby. The petrographic analyses indicate that the studied Injana sandstones are immature mineralogically because of their content of unstable constituents, such as lithic fragments and feldspars. In addition, the presence of such fresh feldspars indicates that the climate in the source area and the deposition site were arid to semi-arid.